Corporate social performance: Does management quality matter? - An, Heng; Boasson, Vigdis; Lei, Lijun; Wu, Qun (Journal of Banking & Finance, 2024)
We use common factor analysis on seven individual management quality measures to extract a management quality factor and examine its relationship with corporate social performance. Using managers’ draft risk during the Vietnam War as an instrumental variable for management quality, we find that firms with higher-quality managers score better in Corporate Social Responsibility (CSR). The cross-sectional results suggest that high-quality managers strategically invest in CSR when potential benefits outweigh the costs. Specifically, the positive relationship between management quality and CSR is more pronounced for firms under fierce product market competition when CSR is crucial for differentiating the firm from its competitors. Moreover, CSR becomes more sensitive to management quality when customer awareness and investor attention are high, increasing the likelihood that CSR enhances customer perception and investor trust. Finally, we find that CSR investment by high-quality managers creates more shareholder value, suggesting that higher-quality managers are more capable of “doing well by doing good.”